Grammatical Competence and Teaching Internship Readiness of Pre-Service Teachers - Fabic, Maria Renita; Magsino, Ara Kayzee; Piol, Melchor; Morillo, Shane; Canosa, Jamaica Maribeth; Bautista, Harren James; De Ramos, Lovelita; Hernandez, Lyra Crizelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the grammatical competence and teaching internship readiness of pre-service teachers at Lemery Colleges, Inc. Specifically, it assessed grammatical competence in terms of subject-verb agreement, pronoun-antecedent agreement, and parts of speech, and evaluated teaching internship readiness in planning and preparation, classroom environment, professionalism, and instruction and assessment strategies. Anchored on the premise that grammatical competence and teaching internship readiness are interrelated components of effective teacher preparation, the study employed a descriptive quantitative research design. A researcher-made questionnaire, validated by experts and tested for reliability using Cronbach’s Alpha, was administered to 115 pre-service teachers selected through purposive sampling. Data were analyzed using weighted mean, Pearson’s r correlation, and Cronbach’s Alpha through SPSS software. The findings revealed that the respondents were Highly Competent in all areas of grammatical competence, particularly in subject-verb agreement, pronoun-antecedent agreement, and parts of speech. Likewise, they were assessed as Fully Ready in all dimensions of teaching internship readiness, including planning and preparation, classroom environment, professionalism, and instruction and assessment strategies. Furthermore, significant positive relationships were found between grammatical competence and teaching internship readiness across all domains, indicating that higher grammatical competence is associated with greater preparedness for teaching practice. Based on the findings, an intervention program in the form of a website entitled Pre-Service Pro: Grammar and Internship Prep was proposed to further enhance the grammatical competence and internship readiness of pre-service teachers. The study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting the development of competent and well-prepared future educators. It contributes to educational and technological sustainability through the enhancement of teacher preparation and the utilization of digital learning resources to support professional development and instructional readiness.
Keywords: Classroom Environment; Grammatical Competence; Instruction and Assessment Strategies; Parts of Speech; Planning and Preparation; Pre-Service Teachers; Professionalism; Pronoun-Antecedent Agreement; Subject-Verb Agreement; Teaching Internship Readiness